2021
DOI: 10.1093/molbev/msab344
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Indicators into the Causes and Consequences of Whole-Genome Duplication Events

Abstract: Whole genome duplications (WGDs) have long been considered the causal mechanism underlying dramatic increases to morphological complexity due to the neo-functionalization of paralogues generated during these events. Nonetheless, an alternative hypothesis suggests that behind the retention of most paralogues is not neo-functionalization, but instead the degree of the inter-connectivity of the intended gene product, as well as the mode of the WGD itself. Here, we explore both the causes and consequences of WGD b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 120 publications
(185 reference statements)
4
17
0
Order By: Relevance
“…Typical examples include genes that encode transcription factors, signal transduction components, or chromatin proteins ( Birchler et al, 2001 ). Subsequently, microRNA genes were also found to be generally retained ( Zhang et al, 2009 ; Abrouk et al, 2012 ; Zhao et al, 2015 ; Peterson et al, 2021 ), which is consistent with their frequent function in modulating transcription factor expression.…”
Section: Mechanisms Of Gene Duplication (And Deletion)supporting
confidence: 58%
“…Typical examples include genes that encode transcription factors, signal transduction components, or chromatin proteins ( Birchler et al, 2001 ). Subsequently, microRNA genes were also found to be generally retained ( Zhang et al, 2009 ; Abrouk et al, 2012 ; Zhao et al, 2015 ; Peterson et al, 2021 ), which is consistent with their frequent function in modulating transcription factor expression.…”
Section: Mechanisms Of Gene Duplication (And Deletion)supporting
confidence: 58%
“…To our knowledge, this is the first report of, and MirMachine the respective tool for, pseudogene-predictions for microRNAs. Pseudogenes, or ‘gene-fossils’, are potentially very useful to determine the rate of gene duplication and follow the evolution of sequence changes in organisms and might be included in studies studying cause and consequences of duplications on microRNAs (Peterson et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…We have also shown that it is possible to use MirMachine’s ‘below cutoff’ predictions for the study of pseudogenes, which could enable better understanding of dosage-level regulation or gene- and genome duplication events, in general (Peterson et al, 2021). Using several so far uncharted vertebrate genomes of either extreme size (axolotl, lungfish) and comparing them to smaller, but secondarily duplicated genomes, we could show that MirMachine works on such large genomes and confirm that the size of assemblies does not matter for the number of microRNAs, but that genome duplication events do.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations